2017
DOI: 10.22596/erj2017.0201.17.25
|View full text |Cite
|
Sign up to set email alerts
|

We Need Resilient School Leaders in the face of Chaos and Complexity

Abstract: We experience some rapid and unexpected changes especially within the incoherent and asunder school policies and implementations that are unsuitable for the demands and expectations of school stakeholders. Furthermore, the internal and other external obstacles and non-ideal situations such as lack of resources, negative school climate, less motivation, organizational conflicts, cultural matters, depersonalization, or resist to change surround the schools today. All these tend to produce serious organizational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
2
0
8
Order By: Relevance
“…Schools are exposed to changes (Limon & Sezgin-Nartgün, 2020) and other unexpected situations very frequently which brings the resilience to their agenda as a prominent issue. Although there is an abundance of research on school leaders' (Day, 2014;Özmusul, 2017), students' (Franklin, 2017) and teachers' resilience (Day & Hong, 2016;Haeussler, 2013;Hong, 2012;Taylor, 2013), few studies investigated the resilience of educational organizations. For example, a study conducted by Sezen-Gültekin (2019) revealed that resilience in higher education institutions had a significant effect on sustainability and was affected by organizational myopia.…”
Section: Organizational Resiliencementioning
confidence: 99%
“…Schools are exposed to changes (Limon & Sezgin-Nartgün, 2020) and other unexpected situations very frequently which brings the resilience to their agenda as a prominent issue. Although there is an abundance of research on school leaders' (Day, 2014;Özmusul, 2017), students' (Franklin, 2017) and teachers' resilience (Day & Hong, 2016;Haeussler, 2013;Hong, 2012;Taylor, 2013), few studies investigated the resilience of educational organizations. For example, a study conducted by Sezen-Gültekin (2019) revealed that resilience in higher education institutions had a significant effect on sustainability and was affected by organizational myopia.…”
Section: Organizational Resiliencementioning
confidence: 99%
“…Contrario a otros liderazgos, el liderazgo resiliente conserva la posición creativa que admite que todo funcione bien, apremiando propósitos, buscando siempre la efectividad (Mendoza, 2020). Otro elemento importante que caracterizan al líder resiliente es que lee y busca constantemente información que le permita vencer dificultades, lo cual lo hace ser pronto, ecuánime y lo ayuda a desarrollarse entre los impedimentos cotidianos (Ozmusul, 2017). El liderazgo resiliente y su perspectiva espiritual se enfoca hacia los valores como la motivación, entereza, respeto, confianza, consideración, emociones, solidaridad y credibilidad, elementos básicos del compromiso, reto y control (Mendoza, 2020).…”
Section: Liderazgo Resilienteunclassified
“…También muestra su gran arrojo al sobresalir ante las barreras a las que se expone la organización, innovando alternativas aun en contra de las circunstancias desfavorables que alteren a la empresa (Ozmusul, 2017). El líder resiliente tiene las capacidades de visionar los riesgos característicos de las calamidades y de explotar los beneficios que se presenten para incentivar a que los demás individuos las disfruten (Navarro et al, 2017).…”
Section: Liderazgo Resilienteunclassified
“…Las evidencias científicas del estudio de resiliencia (Chen, 2016), describen que estudiantes chinos con determinada personalidad resiliente afrontan exigencias académicas y personales para ser exitosos, lo cual sucede en otras poblaciones académicas (Brouskeli, Kaltsi y Loumakou, 2018). El estudio de Dutra-Thomé, Siqueira y Koller (2016), demostró que los estudiantes que aspiran el desarrollo laboral necesitan mayor preparación psicológica para abordar exigencias académicas durante el proceso de desarrollo; esto obedece a la teoría de liderazgo para el éxito resiliente (Ozmusul, 2017), la cual exigen que se desarrollen la mentalidad resiliente, emocionalidad, sociabilidad, ética y aptitudes físicas resilientes. Sin embargo, en la universidad son esenciales el desarrollo de los valores que acompañen la culturización y maduración de la resiliencia (Stanley et al, 2015).…”
Section: Las Competencias Humanísticas: Proactividad Y Resilienciaunclassified